Proyeksi Data dan Analisis Sentimen Penggunaan Vaksin di Kabupaten Indragiri Hulu Berbasis Machine Learning - Ahmad Rizky Andriawan; Mustakim Mustakim (Jurnal Sistem Komputer dan Informatika (JSON), 2021)
Sentiment analysis is research that processed used computer that comes from opinion and emotion wich realized in shape of text. The method that used to analyze sentiment is using Text Mining used for mining the text in order to get comprehension about the important aspect. Text Mining done at social media Twitter. This research analyze public sentiment related with vaccination. Step of Preprocessing contains Crawling Data, Cleaning, Filtering, Stemming, TF-IDF, and labeling. Result from labeling and percentage calculation get percentage that Positive Sentiment is 29.17%, Negative Sentiment is 55.09% percentage, and Neutral is 15.74% percentage. Could be seen that Indonesian public still given many Negative Comments related with vaccination. Result of K-NN calculation with K-9 generate the accuracy is 84.53%.